2011
DOI: 10.4067/s0717-95022011000200002
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Study on the Descent of Testis in Prenatal Goat (Capra hircus)

Abstract: SUMMARY:A study was conducted on 70 embryo/ foetii of goats to observe the descent of testis. These foetii were grouped into I (0-30 days), II (31-60 days), III (61-90 days), IV (91-120days) and V (121 days up to term, having 14 embryos/ foetii in each group. The genital ridge was observed at 1.2cm CRL (23 day) on the ventromedial aspect of mesonephros. At 42 nd day, the genital ridge developed into cylindrical structure, the testis, located in the middle of metanephros. The abdominal migration was completed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Gubernaculum has been shown to be innervated by genitofemoral nerve. Immunohistochemical studies using androgen receptor expression and estrogen receptor knock-out (ERKO) have thrown light on the details of differentiation of the mesenchyme and the time of appearance of skeletal and smooth muscle within gubernaculum In goats, gubernaculum appeared as solid mass of highly eosinophilic mesenchymal cells, with spherical or ovoid nuclei at 56 th day of gestation then became vascular and further differentiated histologically by 108 th day of gestation [12]. Histological analysis of the gubernaculum of pigs ranging from 53 to 116 days of gestation revealed that they consisted of primitive mesenchymal cells with an abundant intercellular material containing glycosaminoglycans [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Gubernaculum has been shown to be innervated by genitofemoral nerve. Immunohistochemical studies using androgen receptor expression and estrogen receptor knock-out (ERKO) have thrown light on the details of differentiation of the mesenchyme and the time of appearance of skeletal and smooth muscle within gubernaculum In goats, gubernaculum appeared as solid mass of highly eosinophilic mesenchymal cells, with spherical or ovoid nuclei at 56 th day of gestation then became vascular and further differentiated histologically by 108 th day of gestation [12]. Histological analysis of the gubernaculum of pigs ranging from 53 to 116 days of gestation revealed that they consisted of primitive mesenchymal cells with an abundant intercellular material containing glycosaminoglycans [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The male reproductive tract has been investigated histologically, ultrastructurally and histochemically in several species including bull (Abdel-Raouf, 1960;Mohammed, 2005;Oni et al, 2021;Staub & Johnson, 2018), camel (Ali et al, 1978;Tingari et al, 1984), rat (Pogach et al, 1993, sheep (Pedrana et al, 2008), goat (Farooqui et al, 2011;Sharma et al, 2011), and domestic fowl (Tingari, 1972;Udoumoh et al, 2021). The goat in general received the least attention (Leal et al, 2018).…”
mentioning
confidence: 99%